Caste and Class Consciousness By Mulk Raj Anand: A Journey of Identity and Social Constraints (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Story of a Young Bhangi Untouchable follows aday in the life of Bakha, an 18 year old Bhangi boy. Written by Mulk Raj Anandin 1935 the fictional story is set in the outcastes' colony outside of anunnamed town during the British occupation. The story is narrated by Bakha whois a hard working boy who never disobeys his father despite his repugnance forhim and his lifestyle. Bakha had worked in the barracks of a British regimentand, "had been caught by the glamour of the 'white man's' life ". TheBritish, or 'Tommies' as Bakha called them, treated him with respect despitehis caste. "Bakha had looked at the Tommies, stared at them with wonderand amazement ... and he had soon become possessed with an overwhelming desireto live their life ". The simplest way for Bakha to imitate the Tommieswas through 'fashun', "by which he understood the art of wearing trousers,breeches, coat, puttees, boots, etc.. ". Bakha is trying to rise above hiscaste by westernizing, yet he receives insults from his friends about hisdress. They chide him for dressing like a sahib and trying to appear to besomething he is not. However, it seems to be the only way he can remove himselffrom his caste. This Story was very well written and kept my attentionthroughout.